Promoting high-quality growth through financial reform in the People’s Republic of China - Huang, Yiping; Wang, Xun; Huang, Anqian (Manila,Philippines Asian Development Bank, 2021)
The report argues that as the economy transitions to focus on high-quality growth, the PRC needs to deepen its financial sector reform. They include measures such as gradually opening up financial markets to foreign and domestic private capital to finance new emerging sectors, strengthening regulatory and supervisory regimes in the face of rapid technological changes, and promoting financial innovations.
Executive Summary - - Introduction - - Overview of Financial Development and Openness - - Financial Reform - - Effects of Financial Repression on Economic Growth and Innovation - - Macro Prudential Policies and Financial Regulatory Framework - - Recent Financial System Developments - - Conclusions and Implications for Further Financial Reforms.
Keywords: Financial institutions -- China; Electronic book